Journal of Montology/ Jurnalul de Montanologie, Vol. XXI - NICULA, Alexandru Sabin (2025)
DOI: https://doi.org/10.52257/23606215_XXI Journal of Montology (J-MONT) is an open access annual journal that aims to present “frontier knowledge” describing how current systems — society, the economy, the environment, agriculture, etc. — work and how they might work in the future. Articles in this journal offer original and innovative scientific research relevant to economic mountain development.